5 - La dynamique de l’enseignement supérieur privé au Cameroun - Nanfosso, Roger Tsafack (Journal of Higher Education in Africa, 2006)
The paper analyses the development of private higher education in Cameroon, in order to highlight its main characteristics. To achieve this, I attempt to analyse the evolution in the functioning of accredited private higher education institutions, and use the technique of descriptive statistics from available official data. The findings allow us to characterize the Cameroonian private higher education system through six main features, related to its structure, share in the national provision of higher education services, creation of job opportunities, mode of funding, levels of student training, and the issue of partnership as a solution to problems faced.